Innovation in Assessment of Civic Education in School - Winarno; Wijianto; Rusnaini (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to develop assessment designs by innovating through digital platforms. This research is instrument development research, also called psychometric methodological research. The results of the study state that innovation in the process of assessing school citizenship education can be done through digital-based assessment. In this study, it was shown about the innovation of developing citizenship attitudes with questionnaires through the Google Forms digital platform. The existence of this innovation makes students more open to answering the questions provided. Students understand more about the importance of normative subjects they learn, considering that students who are the subjects in this study are vocational high school students who have a tendency to be interested in subjects that are practical, not normative subjects.